A ANALYZING ICON, INDEXES, AND SYMBOL IN THE MOVIE FORREST GUMP USING PEIRCE’S SEMIOTIC THEORY - Via Ingrid Anda Resta; Ivan Achmad Nurcholis (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This article examines the intricate meanings within the film Forrest Gump through the lens of Charles Sanders Peirce’s semiotic theory, focusing on icons, indexes, and symbols. While prior studies have highlighted the film's thematic richness, a comprehensive analysis of its semiotic components is lacking. This research employs a qualitative approach, analyzing the film itself as the primary data source to identify and interpret signs in relation to overarching themes. Findings reveal a dynamic interplay among icons, such as the recurring feather, which evokes deep emotional responses; indexes like the Vietnam War, which ground the narrative in reality; and symbols, represented by the character of Forrest, embodying ideas of innocence and resilience. The study concludes that understanding these semiotic elements enhances our appreciation of the film's narrative complexity and emotional resonance. Future research could further explore the film's musical and auditory dimensions within a semiotic framework, providing a more holistic view of its storytelling techniques.